2015
DOI: 10.1364/ol.40.004058
|View full text |Cite
|
Sign up to set email alerts
|

Strong Raman-induced noninstantaneous soliton interactions in gas-filled photonic crystal fibers

Abstract: We have developed an analytical model based on the perturbation theory in order to study the optical propagation of two successive intense solitons in hollow-core photonic crystal fibers filled with Raman-active gases. Based on the time delay between the two solitons, we have found that the trailing soliton dynamics can experience unusual nonlinear phenomena such as spectral and temporal soliton oscillations and transport towards the leading soliton. The overall dynamics can lead to a spatiotemporal modulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Besides its fundamental interest, optical fibers and waveguides [29] turn out to be ideal testbeds for the experimental verification of our predictions, thanks to the easily tailorable Raman response function, as well as other recently investigated mechanisms involving liquid or gas-filled photonic crystal fibers (PCF), as well as surface plasmon polariton systems [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 83%
“…Besides its fundamental interest, optical fibers and waveguides [29] turn out to be ideal testbeds for the experimental verification of our predictions, thanks to the easily tailorable Raman response function, as well as other recently investigated mechanisms involving liquid or gas-filled photonic crystal fibers (PCF), as well as surface plasmon polariton systems [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 83%
“…we have found that a factor of 1 2 » might be used to correct the overestimated value of g 1 , resulting from using the zeroth-order Taylor approximation. The treatments of the dynamics of the trailing pulse 'probe' 2 y are presented in sections 3.1 and 3.2, when it is a weak long pulse and strong ultrashort soliton, respectively [53,54]. The study of the pump-probe dynamics will prove crucial in the future understanding of the essential building blocks of supercontinuum generation in Raman-active gases when excited by ultrashort pulses [69,75].…”
Section: R W mentioning
confidence: 99%
“…Gas-filled HC-PCFs with Kagome lattice have become a powerful alternative for solid-core PCFs especially for nonlinear applications [42]. The low-loss wide transmission window, the pressure-tunability dispersion, and the variety of different gases with special properties have offered several opportunities for demonstrating new nonlinear applications [43] such as Stokes generation with a drastical reduction in Raman threshold [44], high harmonic generation [45], efficient deep-ultraviolet radiation [46], ionization-induced soliton self-frequency blueshift [47][48][49][50], strong asymmetrical SPM, universal modulational instability (MI) [51], parity-time symmetry [52], and temporal crystals [53,54]. The subject of this review is to present in detail some of these applications, especially those which involve soliton dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their relative amplitudes and phases, the two solitons may attract or repel each other. More recently, the effects of Raman scattering on two interacting optical solitons have been studied [6][7][8][9]. In all of these studies, optical pulses were assumed to remain linearly polarized during their propagation inside the optical fiber, and a scalar nonlinear Schrödinger (NLS) equation was used to describe the nonlinear interaction between two temporally separated solitons.…”
Section: Introductionmentioning
confidence: 99%